Nanoindentation characterization of aging gradient of mastic in asphalt mixtures. (30th July 2019) - Yao, Zeheng; Lu, Guilin; Yang, Jun; Gong, Minghui; Tang, Zhiyun; Xue, Jiayue; Zhang, Xiaorui
Highlights: Clarify the effects of mixture gradation and polishing on nanoindentation results. Characterize the age-hardening behavior of asphalt mixtures using nanoindentation. Describe the vertical aging gradient in asphalt mixtures by nanoindentation. Abstract: Understanding the aging behavior of asphalt mixtures is of great significance to the design, construction and maintenance of asphalt pavements. Numerous studies have been conducted on the aging phenomenon and its effects on mixture properties. However, conventional testing methods focus mainly on the global view or average value of the performance of aged mixtures, while the inner aging gradients are seldom addressed. The aging gradient, referring to the differences of aging effects in asphalt mixtures due to different accessibilities to aging conditions, represents the true aging behavior of asphalt mixtures. Hence, a micromechanical testing technique, nanoindentation, was used in this paper to investigate this issue. The effects of mixture gradation and polishing in sample preparation process on nanoindentation results were explored first. Then the vertical changes of modulus of asphalt mastic in asphalt mixture samples were characterized by nanoindentation to describe the aging gradient in different aged mixture samples. Dynamic modulus test was also performed for data supplement and comparison. Results show that gap-graded mixtures are suitable for nanoindentation test and a careful and standard polishing treatment will not affect the reliability of nanoindentation data. Nanoindentation can well characterize the age-hardening behavior of asphalt mastic and the aging gradient in long-term aged asphalt mixtures is approximately in a logarithmic curve form. Nanoindentation modulus results indicate that 8d of laboratory long-term aging in this paper can only affect the upper sections of dense asphalt mixtures. This paper suggests that nanoindentation can achieve a quantitative, mechanical and precise characterization of aging gradient in asphalt mixtures and is therefore promising in further research of asphalt materials.